Effects of Dietary Zinc Sources on Growth Performance and Gut Health of Weaned Piglets - Diao, Hui; Yan, Jiayou; Li, Shuwei; Kuang, Shengyao; Wei, Xiaolan; Zhou, Mengjia; Zhang, Jinxiu; Huang, Chongbo; He, Peng; Tang, Wenjie (Frontiers in Microbiology, 2021)
The present study aimed to investigate the effects of dietary zinc sources on the growth performance and gut health of weaned piglets. In total, 96 Duroc × Landrance × Yorkshire (DLY) weaned piglets with an initial average body weight of 8.81 ± 0.42 kg were divided into four groups, with six replicates per treatment and four pigs per replicate. The dietary treatment groups were as follows: 1) control group, basal diet; 2) zinc sulphate (ZnSO4) group, basal diet + 100 mg/kg ZnSO4; 3) glycine zinc (Gly-Zn) group, basal diet + 100 mg/kg Gly-Zn and 4) zinc lactate group, basal diet + 100 mg/kg zinc lactate. The whole trial lasted for 28 days. Decreased F/G was noted in the Gly-Zn and zinc lactate groups (P < 0.05). The zinc lactate group had a lower diarrhoea rate than the control group (P < 0.05). Moreover, the ZnSO4, Gly-Zn and zinc lactate groups had significantly higher apparent total tract digestibility of dry matter (DM), crude protein (CP), ether extract (EE), crude ash and zinc than the control group (P < 0.05). The Gly-Zn and zinc lactate groups had higher jejunal villus height and a higher villus height:crypt depth ratio than the control group (P < 0.05). In addition, the ZnSO4, Gly-Zn and zinc lactate groups had a significantly lower mRNA expression level of jejunal ZRT/IRT-like protein 4 (ZIP4) and higher mRNA expression level of jejunal interleukin-1β (IL-1β) than the control group (P < 0.05). The mRNA expression level of jejunal zinc transporter 2 (ZNT2) was higher and that of jejunal Bcl-2 associated X protein (Bax) was lower in the Gly-Zn and zinc lactate groups than in the control group (P < 0.05). Moreover, the zinc lactate group had a higher count of Lactobacillus spp. in the caecal digesta and higher mRNA expression levels of jejunal occludin and mucin 2 (MUC2) than the control group (P < 0.05). In conclusion, dietary supplementation with 100 mg/kg ZnSO4, Gly-Zn or zinc lactate could improve the growth performance and gut barrier function of weaned piglets. Dietary supplementation with organic zinc, particularly zinc lactate, had the best effect.